Pentecostalism, mainline Protestantism, and the A.C. Valdez Jr. healing campaign in Winnipeg, 1952 - McLean, Brian (2014)
The purpose of this study is to explore an aspect of Canadian religious history that has been largely neglected by historians, namely the relationship between conservative Protestant Christianity and mainline Protestantism from the early twentieth century to the 1960s, and address critical questions related to the continued presence of conservative Protestant Christianity in Canadian society. Through its focus on relations between conservative and mainline Protestants in Winnipeg, it will examine whether the abandonment of evangelicalism in mainline Protestant churches contributed to the growth of groups like the Pentecostal movement throughout the first half of the twentieth century. It will investigate whether Pentecostals and other evangelical groups filled the void vacated by the liberalizing mainline denominations. And finally, it will consider whether the continued growth in membership of conservative Protestant churches in the middle decades of the twentieth century was indeed influenced by conflict between liberal and conservative Protestants.